How Financial Ratios Affect Company Efficiency - Serang, Robert Alex; Fitriani, Azizah; Afif, Ahmad Sururi; Suyadi, Suyadi (Program Pascasarjana STIE Amkop Makassar, 2023)
The subject of this investigation is a manufacturing firm that is publicly traded on the Indonesia Stock Exchange. The goal of this research is to investigate and assess the impact of leverage (DER), liquidity (CR), and profitability (ROA) on firm efficiency. (TATTOO). The sample count is a total of 18 manufacturing companies obtained through the purposive sampling technique. This study employs a causality study design. A descriptive quantitative study was used in the research, and the data was analyzed using multiple linear regression methods. This study's findings suggest that: 1) DER has a negative and significant effect on TATO, 2) CR has a non-significant positive effect on TATO, and 3) ROA has a positive and significant effect on TATO. Keywords: Company Efficiency; leverage; Liquidity.